Penerapan Uji Tuntas HAM dalam Korporasi Pada Perkebunan Kelapa Sawit Di Indonesia - Muhamad Aljabar Putra; Alfitra Alfitra (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThe process of implementing the Human Rights Due Diligence carried out by Corporations in the Oil Palm Sector in Sumatra and Kalimantan has a number of problems. Analysis and criticism of the Minister of Agriculture Regulation No. 1 of 2015 concerning Indonesian Sustainable Palm Oil which is considered to have failed in regulating and regulating the principles of human rights due diligence, so that the impact of the implementation of human rights due diligence is ineffective. The form of weakness in the a quo regulation is evidenced by the existence of excess strength from the ISPO Commission which causes no checks and balances related to the implementation of Due Diligence. The type of research used is qualitative, with a normative-doctrinal research approach, in which there are elements of the statutory approach and conceptual approach used to find out the ideal mechanism for implementing the Human Rights Due Diligence on Corporations in the palm oil sector. This research proves that the implementation of human rights due diligence at this time still needs to be done various improvements because the current mechanism does not accommodate the principle of transparency, the existence of super power authority from the ISPO Commission, the creation of depedency practices within the ISPO internally. Absolutism of authority by the ISPO commission can disrupt the neutrality and professionalism of the implementation of human rights due diligence. This has caused many corporations to disobey Due Diligence and is directly proportional to the increase in the number of human rights violations by corporations.Keywords: Human Rights Due Diligence, Corporations, Indonesian Sustainable Palm Oil